Orthodontic Management of Bucal Canine Ectopic and Lost of Space Permanent Molar: A Case Report - Paramma, Zilal I (Hasanuddin University, 2022)
Objective : The aim of this article reports the orthodontic treatment planning carried out with a 28-year old female patient with aesthetic and functional complaints. She presented a bucal canine ectopic and an early lost permanent first molar.Methods: Orthodontic treatment for correction bucal canine ectopic and space of lost first molar permanent. Correction bucal canine ectopic by extraction premolar teeth and lost permanen first lower molar was corrected by mesialization second lower molar in addition elastic class 2. Results: Bucal canine reposition in normally arch and space of permanen first lower molar changed by second lower molar.Conclusion: Orthodontic treatment can achieve a new appreance facial and functional mastication normally.